2017
DOI: 10.1002/2211-5463.12231
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles ofBrMYBtranscription factors related to glucosinolate biosynthesis and stress response in eight subspecies ofBrassica rapa

Abstract: Brassica rapa is a polyploid species with phenotypically diverse cultivated subspecies. Glucosinolates (GSLs) are secondary metabolites that contribute to anticarcinogenic activity and plant defense in Brassicaceae. Previously, complete coding sequences of 13 BrMYB transcription factors (TFs) related to GSL biosynthesis were identified in the B. rapa genome. In the present study, we investigated GSL content and expression levels of these BrMYB TFs in 38 accessions belonging to eight subspecies of B. rapa. Twel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Detailed information including the chemical name and side chains is found in Refs. [ 8 , 19 , 22 , 23 , 24 ]. An abundance of GRH was well demonstrated in previous studies on radish roots [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Detailed information including the chemical name and side chains is found in Refs. [ 8 , 19 , 22 , 23 , 24 ]. An abundance of GRH was well demonstrated in previous studies on radish roots [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the side chains of the core structures are modified by oxidation, elimination, alkylation or esterification in the aliphatic and indolic groups [ 14 ]. Aliphatic GSLs are the most abundant, at about 57–97% of the total GSL content, while aromatic GSLs are minor components in Brassica species [ 24 , 25 , 26 ]. The GSLs of the aliphatic and aromatic groups have unique properties for human health and livestock and have roles in oncogenesis, disease, and nutrition [ 27 ].…”
Section: Metabolic and Regulatory Pathways Of Gsl Biosynthesismentioning
confidence: 99%
“…Consequently, variations in gene length (in base pair) and nonsynonymous amino acid sequences are caused by polymorphisms in the downstream C-terminal region. We have identified and reported the conserved R2R3 MYB DNA-binding domains of 13 MYB TFs related to GSL biosynthesis in B. rapa [ 16 , 24 ]. A phylogenetic tree was constructed using the amino acid sequences of 61 R2R3 MYB DNA-binding domains containing A. thaliana to elucidate evolutionary relationships ( Figure 3 ).…”
Section: Myb Tfs Involved In Gsl Biosynthesis In Genome-sequenced mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Seo et al (2016) found that in Brassica rapa ( Br ) genome, BrMYB28 genes were identified as three orthologous copies to Arabidopsis thaliana ( AtMYB28 ). Particularly overexpression of three BrMYB28 genes such as BrMYB28.1 , BrMYB28.2 and BrMYB28.3 are responsible for the higher synthesis of GSL [ 9 ]. Subsequently, several activated products of GSLs are beneficial to human and animal health [ 10 ].…”
Section: Introductionmentioning
confidence: 99%